A set of technological devises for replacing collimators in horizontal channels of reactor - V. A. Libman; V. F. Razbudey; Yu. B. Shevchenko (Ядерна фізика та енергетика)
Devices of original construction for replacing collimators are described in this paper. Special attention has been focused on technology of moving off “outdated” collimators that have been stuck inside a channel. Carried out set of devices has been used effectively in experiments at the reactor of the Institute for Nuclear Research of NAS of Ukraine and may be used at other reactors.